2011
DOI: 10.1093/eurheartj/ehr225
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of genome-wide association studies signals for lipids, diabetes, and coronary heart disease: Cardiovascular Biomarker Genetics Collaboration

Abstract: AimsTo evaluate the associations of emergent genome-wide-association study-derived coronary heart disease (CHD)-associated single nucleotide polymorphisms (SNPs) with established and emerging risk factors, and the association of genome-wide-association study-derived lipid-associated SNPs with other risk factors and CHD events.Methods and resultsUsing two case–control studies, three cross-sectional, and seven prospective studies with up to 25 000 individuals and 5794 CHD events we evaluated associations of 34 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 53 publications
(77 reference statements)
3
55
0
3
Order By: Relevance
“…52 However, 9p21 does not seem to be associated with risk for CAD in blacks. 53 In these studies, as in a more recent study, 54 the 9p21 risk variant is consistently shown to act independently of known risk factors. Fine mapping of the 9p21 risk region shows that it is confined to a 58 000-bp region with several SNPs showing significant association with CAD, all in linkage disequilibrium with rs4977574.…”
Section: P21: the First Genetic Risk Variant For Cad Whose Function mentioning
confidence: 64%
“…52 However, 9p21 does not seem to be associated with risk for CAD in blacks. 53 In these studies, as in a more recent study, 54 the 9p21 risk variant is consistently shown to act independently of known risk factors. Fine mapping of the 9p21 risk region shows that it is confined to a 58 000-bp region with several SNPs showing significant association with CAD, all in linkage disequilibrium with rs4977574.…”
Section: P21: the First Genetic Risk Variant For Cad Whose Function mentioning
confidence: 64%
“…1) [5,8,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Подробные результаты этих 9 метаанализов представлены на рис.…”
Section: результатыunclassified
“…В отдельных метаанализах, где объемы выборки не достигали 186000 участников, аллель воздействия для каждого МНП также был связан с соответственно более низким риском ИБС (рис. 2) [8][9][10]17,20,21,[27][28][29][30][31][32][33][34][35][36][37]. Подробные результаты этих 9 метаанализов представ-лены на рис.…”
Section: результатыunclassified
“…ANGPTL3 rs2131925 was associated with a mean reduction in plasma TG levels (Teslovich et al, 2010). In another report, ANGPTL3 rs12042319 was associated with lower levels of low-density lipoprotein cholesterol, TG and IL-6 (Angelakopoulou et al, 2012). These studies clearly showed there is a genetic link between ANGPTL3 and regulation of lipid metabolism, which suggested that variation in ANGPTL3 might affect its function.…”
Section: Introductionmentioning
confidence: 90%